2020
DOI: 10.1080/09638288.2020.1800839
|View full text |Cite
|
Sign up to set email alerts
|

Early termination in interdisciplinary pain rehabilitation: numbers, timing, and reasons. A mixed method study

Abstract: Purpose: To analyse the number of, timing of, and reasons for early termination of interdisciplinary pain rehabilitation (IPR). Methods: A multicentre study in two Dutch rehabilitation centres with a mixed method design. Quantitative part: retrospective patient file review of all IPR patients. Qualitative part: 20 semi-structured patient interviews with early IPR terminators. Results: One hundred and thirty-seven of 428 participants (31.3%) had terminated IPR early, of which almost 30% had a positive reason. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…By its very nature, this is a field with significant risk for publication bias because results are unlikely to be reported if the group visit model is not sustainable in the first place. Several GMV studies have reported early termination rates of 30% to 75% (10, 11). This demonstrates the need for additional information regarding patient interest in GMVs to improve retention rates and tailor content.…”
Section: Introductionmentioning
confidence: 99%
“…By its very nature, this is a field with significant risk for publication bias because results are unlikely to be reported if the group visit model is not sustainable in the first place. Several GMV studies have reported early termination rates of 30% to 75% (10, 11). This demonstrates the need for additional information regarding patient interest in GMVs to improve retention rates and tailor content.…”
Section: Introductionmentioning
confidence: 99%